Willingness to pay for improved household solid waste collection in Blantyre, Malawi - Hanke Ndau; Elizabeth Tilley (Economies, 2018)
Insufficient staff, inappropriate collection vehicles, limited operating budgets and growing, hard to reach populations mean that solid waste management remains limited in most developing countries; Malawi is no exception. We estimated the willingness to pay (WTP) for two hypothetical solid waste collection services. Additionally, we tested the impact of the WTP question positioning relative to environmental perceptions on respondents' WTP. The first scenario involved a five minute walk to a disposal facility; the second scenario involved a 30 min walk. Additionally, the order of the question was randomized within the questionnaire. A WTP value of K1780 was found for the five minute walk scenario when the question was placed first, and K2138 when placed after revealing the respondent's perceptions on the environment. In the 30 min walk scenario, WTP was K945 when placed first and K1139 when placed after revealing the respondent's perceptions on the environment. The estimated values indicate that there is both a willingness to pay for solid waste services and that there are at least two options that would be acceptable to the community; a pilot scale implementation would be required to validate the hypothetical values, especially given the dependency on problem framing. Community financing should be considered as a sustainable approach to solid waste management in underserved areas.
Keywords: D12; D64; I10; I15; Q20; 330; solid waste; Malawi; WTP; dichotomous choice; Africa; service delivery